Micro-expansion glue-powder-free high-adhesion cement-based self-leveling material and preparation method thereof
By controlling the ratio of anhydrite to sulphoaluminium cement and compounding tartaric acid and sodium gluconate as a retarder, optimizing the filler composition and mixing time, the cracking and bonding strength problems of cement-based self-leveling materials are solved, and a balance between high fluidity and high strength is achieved, making it suitable for large-scale production.
Patent Information
- Application Number
- CN202511244262.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-02
- Publication Date
- 2025-10-24
AI Technical Summary
Existing cement-based self-leveling materials are prone to cracking during the hydration and hardening stage, have insufficient bonding strength, poor fluidity, and unstable production processes, making it difficult to meet the needs of large-scale production.
By limiting the mass ratio of anhydrite to sulphoaluminium cement to (0.3-0.4):1, the formation rate of ettringite is precisely controlled, tartaric acid and sodium gluconate are combined to form a retarder, and the filler composition and mixing time are optimized to ensure a balance between micro-expansion, bonding strength and fluidity.
The anti-cracking performance of the micro-expanding glue-free high-adhesion cement-based self-leveling material has been improved, the 28d bonding strength has reached 3.6MPa, the fluidity retention rate is high, the production cost has been reduced, and it is suitable for large-scale production.
Smart Images

Figure BDA0005577388350000051 
Figure BDA0005577388350000052 
Figure BDA0005577388350000061
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the field of building materials, and particularly relates to a micro-expansion non-gelatin powder high-adhesion cement-based self-leveling material and a preparation method thereof. BACKGROUND
[0002] The cement-based self-leveling material is a kind of efficient ground leveling material, which is widely used in building ground engineering. It has the advantages of simple construction, good fluidity and high strength, and can quickly realize the leveling and high strength requirements of the ground. However, the existing cement-based self-leveling material still has some problems in practical application, which needs to be improved.
[0003] The existing cement-based self-leveling material generally cracks due to cement shrinkage stress during hydration and hardening, thereby weakening the adhesion strength with the base layer. Although the adhesion and crack resistance can be improved by adding redispersible latex powder, such as the micro-expansion cement-based self-leveling mortar controlled by thiocyanate disclosed in Chinese patent application CN118515463A, the preparation raw materials of which include redispersible latex powder, the introduction of the latex powder will cause the increase of cost, the decrease of durability and environmental problems. On the other hand, the single retarder system used to prolong the operable time cannot meet the requirements of fluidity retention and later strength development at the same time. At the same time, the ratio of gypsum to cement lacks precise control, resulting in unstable expansion effect, which cannot reliably offset the shrinkage and achieve high adhesion strength. In addition, the existing production process does not form a standardized parameter for mixing time, and the material uniformity is insufficient, resulting in batch-to-batch fluctuations in product performance, which is difficult to meet the needs of large-scale stable production.
[0004] In summary, the existing cement-based self-leveling material still has deficiencies in micro-expansion, adhesion strength, fluidity retention, raw material selection and production process. Therefore, it is urgent to develop a cement-based self-leveling material with micro-expansion, high adhesion strength, excellent fluidity retention, and suitable for large-scale production, and a preparation method thereof, to meet the needs of practical engineering. SUMMARY
[0005] In order to solve the above technical problems, the first aspect of the present application provides a micro-expansion non-gelatin powder high-adhesion cement-based self-leveling material, the preparation raw materials of which include, in terms of mass fraction, 270-300 parts of Portland cement, 100-120 parts of sulphoaluminate cement, 30-40 parts of hard gypsum, 500-610 parts of filler, 1-2 parts of water reducing agent, 0.5-1 part of defoaming agent, 0.5-1 part of stabilizer, 1-1.5 parts of shrinkage reducing agent, and 1.4-1.6 parts of retarder.
[0006] As an implementable case, the strength of the Portland cement includes one of 42.5, 42.5R, 52.5 or 52.5R.
[0007] Further, the strength of the silicate cement is 42.5.
[0008] As an implementable case, the mass ratio of the hard gypsum and the sulphoaluminate cement is (0.3-0.4):1.
[0009] Further, the particle size of the hard gypsum is 1000-2000 mesh.
[0010] The present application limits the mass ratio of the hard gypsum and the sulphoaluminate cement to (0.3-0.4):1, controls the generation rate and amount of ettringite accurately, causes moderate micro-expansion in the initial hardening stage to offset the cement hydration shrinkage, ensures that the 28d dimensional change rate is within +0.009%, avoids cracking and significantly improves the bonding strength with the base layer; if the sulphoaluminate cement is excessive, the gypsum is insufficient, the expansion is insufficient, the system shows net shrinkage and is accompanied by cracking; if the hard gypsum is excessive, the ettringite is excessively generated, causes excessive early expansion, causes the 20min fluidity loss to be below 126mm, is not conducive to construction operation, and the ratio range ensures the micro-expansion effect, does not need to add additional powder to achieve 28d bonding strength ≥3.6MPa, takes into account the strength, fluidity retention rate and production cost, and is suitable for large-scale stable production.
[0011] As an implementable case, the filler includes fly ash, quartz sand and calcium powder.
[0012] Further, the mass ratio of the fly ash, the quartz sand and the calcium powder is (3-4):(5-6):(15-20).
[0013] Further, the fly ash is first-grade fly ash.
[0014] Further, the calcium powder is heavy calcium carbonate, and the particle size is 300-400 mesh.
[0015] Further, the particle size of the quartz sand is 70-140 mesh.
[0016] As an implementable case, the water reducing agent is a polycarboxylic acid water reducing agent.
[0017] The polycarboxylic acid water reducing agent mainly plays a dual role of dispersion and water reduction and flow retention, significantly reduces the flocculation between silicate cement and sulphoaluminate cement particles through electrostatic repulsion and steric hindrance effect, reduces the slurry viscosity, and thus ensures that the initial fluidity is >130mm; meanwhile, the slow-release structure can delay the hydration heat release, inhibit the early strength growth too fast, and achieve the balance of C30 strength grade and high bonding performance without additional powder.
[0018] As an implementable case, the defoaming agent is a powder defoaming agent.
[0019] Further, the type of the powder defoaming agent is DF06 powder defoaming agent.
[0020] As an implementable case, the retarder comprises tartaric acid and sodium gluconate.
[0021] Further, the mass ratio of the tartaric acid and the sodium gluconate is (7-8):(7-8).
[0022] Further, the sodium gluconate is purchased from Shandong Fuyang Biological Technology Co., Ltd.
[0023] The present application solves the defects of single retarder by compounding tartaric acid and sodium gluconate in a mass ratio of (7-8):(7-8) to form a retarding system. When only tartaric acid is used, the workable time can be prolonged, but the late strength development is significantly inhibited. When only sodium gluconate is used, the final strength is not affected, but the flow degree maintaining effect is insufficient. When tartaric acid and sodium gluconate are compounded, the two retarders produce a synergistic adsorption-complexing effect on the surface of cement particles, delaying the hydration of aluminate phase, thereby maintaining the flow degree while ensuring that the 28d compressive strength is ≥34MPa, achieving the balance between flowability and mechanical properties. When the amount of tartaric acid is too high, the early hydration of cement will be excessively inhibited, the 28d compressive strength will decrease, the formation of ettringite will be too slow, resulting in insufficient micro-expansion compensation, and the initial setting time will be abnormally prolonged. If the amount of sodium gluconate is too high, the early ettringite formation will be hindered due to excessive complexation of Ca 2+ , the 28d bonding strength and the paste viscosity will decrease, and the adsorption sites will compete with tartaric acid, destroying the synergistic effect and causing the uniformity of the system to decrease.
[0024] The second aspect of the present application provides a preparation method of a micro-expanding glue-free high-bonding cement-based self-leveling material, comprising: mixing silicate cement, sulphoaluminate cement, hard gypsum, filler, water reducing agent, defoaming agent, stabilizer, shrinkage reducing agent and retarder according to mass fraction, to obtain the micro-expanding glue-free high-bonding cement-based self-leveling material.
[0025] Advantages
[0026] (1) The present application realizes the micro-expanding property of the system by limiting the mass ratio of hard gypsum and sulphoaluminate cement to (0.3-0.4):1, effectively offsets the shrinkage of cement hydration, significantly improves the anti-cracking performance, and enhances the bonding strength of the product and the construction base, with a 28d bonding strength of 3.6MPa.
[0027] (II) The tartaric acid and sodium gluconate are selected as the retarder in the application, and the mass ratio of tartaric acid and sodium gluconate is (7-8):(7-8), which ensures the flow degree retention rate, the flow degree is greater than or equal to 140 mm after 20 min, avoids the strength loss caused by single doping, and the 28d compressive strength reaches 36 MPa.
[0028] (III) Shandong Fuyang industrial-grade sodium gluconate is selected as the retarder in the application, and the synergistic effect of tartaric acid and sodium gluconate is better than that of other manufacturers' products, which ensures the flow degree stability and mechanical strength development.
[0029] (IV) The application realizes micro-expansion by precisely controlling the gypsum ratio, and high bonding strength is achieved without additional addition of glue powder, the 28d bonding strength is 3.6 MPa, the cost is reduced, and the formula is simplified.
[0030] (V) The production line stirring time is determined to ensure the mixing uniformity, and the product quality stability and production efficiency are improved. DETAILED DESCRIPTION
[0031] The test items and test methods involved in the application are as follows:
[0032] 1. Flow degree test (test according to JCT 9857.3.2)
[0033] On a test plate with an area greater than 300mm*300mm, a metal or circular pipe with an inner diameter of 30mm and a height of 50mm is placed in the center of the test plate, and an appropriate amount of cement-based self-leveling is poured into the pipe until the upper edge of the pipe is flush with the pipe, the excess slurry is scraped off, and the test pipe is lifted 50-100mm within 2s, and kept for 10-15s to automatically level. The self-leveling circular diameter of the test is tested after 4min, and three groups are taken as the average value, that is, the initial flow degree value (>130mm). After the remaining slurry is placed in the mixer for 20min, it is slowly stirred for 15s, and the above steps are repeated to test the flow degree after 20min, that is, the flow degree value after 20min (>30mm). After 20min, the greater the flow degree, the longer the operation time.
[0034] 2. Dimensional change rate (test according to JCT 9857.5)
[0035] 3. Bonding strength (test according to JCT 9857.4)
[0036] 4. Compressive and flexural strength (test according to JCT 9857.7)
[0037] 5. Circular ring method for testing anti-cracking (used for auxiliary verification of the proportion of sulfur aluminum and gypsum)
[0038] Ring method: use 425x305x100mm ring, take the right amount of mixed cement self-leveling mortar into the test mold, after hardening, remove the outer ring, place in the 40℃ oven for high temperature cracking test, observe whether the hardened mortar ring appears cracks after 28d.
[0039] Ring method test principle of mortar cracking: stress limited shrinkage: internal ring restriction, the mortar ring will receive the tensile resistance of the internal ring, when the tensile strength of the mortar ring cannot resist the tensile resistance, different stress shrinkage cracks will appear along the ring.
[0040] The raw material information involved in the application is as follows:
[0041] Portland cement: strength 42.5 cement, purchased from Anhui Conch Cement Co., Ltd.
[0042] Sulphoaluminate cement: self-stress sulphoaluminate cement, purchased from Shanxi Yangquan Tianlong Engineering Materials Co., Ltd.
[0043] Hard gypsum: 1250 mesh hard gypsum, purchased from Hengtai International Trade Co., Ltd.
[0044] Fly ash (filler): first-class fly ash, purchased from Shanghai Sici Building Materials Co., Ltd.
[0045] Quartz sand (filler): 70-140 mesh quartz sand, purchased from Fengyang County Zhenggong Mining Industry Co., Ltd.
[0046] Calcium powder (filler): 325 mesh heavy calcium carbonate, purchased from Guangfu Building Material Refining Co., Ltd.
[0047] Water reducing agent: 325C polycarboxylic acid high efficiency water reducing agent, supplier is Swiss Sika Company.
[0048] Defoaming agent: DF06 powder defoaming agent, purchased from Shanghai Yingshan New Material Technology Co., Ltd.
[0049] Shrinkage reducing agent: P80 shrinkage reducing agent, brand is Sailikanni.
[0050] Stabilizer: STA400 suspension stabilizer, supplier is Germany BASF Company.
[0051] Tartaric acid (retarder): Li + Tartaric acid retarder, purchased from Nanjing Stebao Trade Co., Ltd.
[0052] Sodium gluconate (retarder): industrial grade sodium gluconate, purchased from Shandong Fuyang Biological Technology Co., Ltd.
[0053] Experimental group one
[0054] The experiment group explores the influence of the ratio of sulphoaluminate cement and hard gypsum on the micro-expanding non-powder high-adhesion cement-based self-leveling material product, and the preparation raw material components and mass fraction information of the product are shown in Table 1, and the performance test results are shown in Table 2.
[0055] The preparation method of the micro-expanding non-powder high-adhesion cement-based self-leveling material is that the preparation raw materials are mixed uniformly according to the mass fraction.
[0056] Table 1
[0057]
[0058] Table 2
[0059]
[0060]
[0061] As can be seen from Tables 1-2, the increase of the use amount of hard gypsum can reduce the shrinkage of the system, reduce the stress shrinkage in different directions of the sample block, thereby increasing the adhesion strength with the base layer.
[0062] When the hard gypsum content increases from 30 parts (3wt%) to 40 parts (4wt%), the system changes from shrinkage to micro-expansion. At the same time, the adhesion strength is greatly improved; when the hard gypsum content increases to 50 parts (5wt%), although the system strength and expansion value are increasing, due to the high specific surface area and the increase of the strength development speed of the system, the fluidity does not meet the index requirements, therefore, the final determination of the hard gypsum content is 3wt% to 4wt% most suitable.
[0063] Experiment group two
[0064] The experiment group explores the influence of the ratio of tartaric acid and sodium gluconate on the micro-expanding non-powder high-adhesion cement-based self-leveling material product, and the product components and mass fraction information are shown in Table 3, and the performance test results are shown in Table 4.
[0065] The preparation method of the micro-expanding non-powder high-adhesion cement-based self-leveling material is that the raw materials are mixed uniformly according to the mass fraction.
[0066] Table 3
[0067]
[0068]
[0069] Table 4
[0070]
[0071] From Table 3-4, it can be seen that using single-component tartaric acid as a retarder can ensure the fluidity, but can weaken the mechanical strength, so that the product still does not reach the standard required strength at 28d; single-component sodium gluconate as a retarder does not affect the late strength, but the effect of maintaining fluidity is not good. When sodium gluconate and tartaric acid are mixed, the effects of both can be ensured. When the tartaric acid exceeds 1 part (0.1wt%), the effect on the mechanical strength of the system is obvious, greatly reducing the speed of the development of the late strength. It is finally confirmed that the mass ratio of tartaric acid and sodium gluconate is (7-8):(7-8), which can ensure the fluidity and also ensure the strength improvement.
[0072] Experiment Group Three
[0073] In this experimental group, the influence of the selection of the sodium gluconate manufacturer on the micro-expanding non-gelatin powder high-bonding cement-based self-leveling material product is explored. The product components and mass fraction information are shown in Table 5, and the performance test results are shown in Table 6.
[0074] The preparation method of the micro-expanding non-gelatin powder high-bonding cement-based self-leveling material is to mix the raw materials uniformly according to the mass fraction.
[0075] Among them:
[0076] In Example 3.1, the sodium gluconate is an industrial-grade sodium gluconate purchased from Shandong Fuyang Biological Technology Co., Ltd.
[0077] In Example 3.2, the sodium gluconate is an industrial-grade sodium gluconate purchased from Shandong Xiyang Sugar Industry Co., Ltd.
[0078] In Example 3.3, the sodium gluconate is an industrial-grade sodium gluconate purchased from Jiangsu Caolie Biological Technology Co., Ltd.
[0079] In Example 3.4, the sodium gluconate is an industrial-grade sodium gluconate purchased from Hebei Chuangzhuyuan Biological Technology Co., Ltd.
[0080] Table 5
[0081]
[0082]
[0083]
[0084]
[0085] From Table 5-6, it can be seen that the industrial grade sodium gluconate of Shandong Fuyang Biological Technology Co., Ltd. can well ensure the flowability and strength improvement when matched with tartaric acid; while the matching efficiency of sodium gluconate of Shandong Xiyang Sugar Industry Co., Ltd., Jiangsu Caiwei Biological Technology Co., Ltd. and Hebei Chuangzhiyuan Biological Technology Co., Ltd. with tartaric acid is not as high as that of the sodium gluconate of Shandong Fuyang Biological Technology Co., Ltd., so the industrial grade sodium gluconate of Shandong Fuyang Biological Technology Co., Ltd. is determined as the optimal choice.
[0086] Experiment group four
[0087] In this experiment group, the uniformity of the stirred material and the time required to achieve uniformity are determined by measuring the initial flowability at different stirring times and different point positions. The time selection is shown in Table 7.
[0088] Test method: The production line corresponding to Example 1.1 is started after all raw materials are added, and the initial flowability of the upper and lower representative points in the filler is tested to represent the uniformity of stirring. The sampling method is to sample the upper surface to represent the upper point, and to sample the discharge port to represent the lower point. The experimental results are shown in Table 8.
[0089] Table 7
[0090]
[0091] Table 8
[0092]
[0093] From Tables 7-8, it can be seen that after stirring for 25 min, the flowability is close to that of the small sample (based on the flowability test of the 1 kg sample prepared in the laboratory after being fully shaken, to compare the differences between the production index and the self-prepared one, to represent some production process errors or to evaluate the stability of the raw materials), and at 30 min, there is basically no difference with the small sample flowability, and with the extension of stirring time, the flowability does not change. Therefore, the stirring time of cement-based self-leveling material on the production line is at least 30 min, and it can be controlled at 30-35 min to ensure uniform mixing of the system.
Claims
1. A micro-expansive, powder-free, high-bonding cementitious self-leveling material, characterized in that, The raw materials are prepared by mixing 270-300 parts of Portland cement, 100-120 parts of sulphoaluminate cement, 30-40 parts of anhydrite, 500-610 parts of filler, 1-2 parts of water reducing agent, 0.5-1 part of defoaming agent, 0.5-1 part of stabilizer, 1-1.5 parts of shrinkage reducing agent and 1.4-1.6 parts of retarder. The retarder comprises tartaric acid and sodium gluconate.
2. The slightly-foamed, powder-free, high-bonding, cementitious self-leveling material according to claim 1, characterized in that, The mass ratio of the anhydrite to the sulphoaluminate cement is (0.3-0.4):
1.
3. The micro-expanding high bond powder-free cementitious self-leveling material according to claim 2, characterized in that, The particle size of the anhydrite is 1000-2000 mesh.
4. The micro-expanding, powder gelatin-free, high-bonding cementitious self- leveling material according to claim 1, wherein, The filler comprises fly ash, quartz sand and calcium powder.
5. The micro-expanding high bond powder-free cementitious self-leveling material according to claim 4, characterized in that, The mass ratio of the fly ash, quartz sand and calcium powder is (3-4):(5-6):(15-20).
6. The micro-expanding high bond powder-free cementitious self-leveling material according to claim 4, characterized in that, The calcium powder is heavy calcium carbonate with a particle size of 300-400 mesh.
7. The slightly-aiiended, non-powdered, high-bond, cementitious, self-leveling material according to any one of claims 1-6, wherein, The defoaming agent is a powder defoaming agent.
8. The micro-expanding, powder gelatin-free, high-bonding, cementitious self- leveling material according to claim 1, wherein, The water reducing agent is a polycarboxylic acid water reducing agent.
9. The micro-expanding, powder gelatin-free, high-bonding, cementitious self- leveling material according to claim 1, wherein, The mass ratio of the tartaric acid to the sodium gluconate is (7-8):(7-8).
10. A process for the preparation of a micro-foamed, non-powdered glue-free, high- bonding cementitious self-leveling material according to any one of claims 1-9, characterized in that, The method comprises the following steps: The raw materials are prepared by mixing 270-300 parts of Portland cement, 100-120 parts of sulphoaluminate cement, 30-40 parts of anhydrite, 500-610 parts of filler, 1-2 parts of water reducing agent, 0.5-1 part of defoaming agent, 0.5-1 part of stabilizer, 1-1.5 parts of shrinkage reducing agent and 1.4-1.6 parts of retarder.
Citation Information
Patent Citations
Thiocyanate-regulated micro-expansive cement-based self-leveling mortar and preparation method thereof
CN118515463A